Comparative analysis of Juchid genealogies according to five lists of “Muizz al-Ansab” - Sabitov Zh.M.; Margulan A.S; Kambarbekova G.A. (Золотоордынское обозрение)
The purpose of the study is to study the genealogy of the Juchids according to the five lists in the «Muizz al-Ansab». The uniformity of the structure of the Muizz al-Ansab lists enables researchers to identify new data in the genealogical chains of the Juchid dynasty. Research materials. During the writing of this article, the researchers engaged in the search for, and collection of, five manuscripts of hte «Muizz al-Ansab». At present, two copies of the list No. 14306 and No. 467 are kept in the British Library in London, manuscript No. 67 is in the National Library of France in Paris, and the latest lists No. 41 and No. 42 are in India at the library of the Muslim University of Aligarh. These manuscripts were compiled in Persian in XV–XIX centuries and represent a genealogical tree of the descendants of Genghis Khan and Timur. Results and scientific novelty. This article presents the translation and analysis of five lists of the «Muizz al-Ansab» which have not been translated for various reasons. We found a large number of differences between the five lists of Muizz al Ansab. Also, unique information was found from different lists (about the daughter of Berke or the genealogy of the Golden Horde Khan Bekbolat, etc.). We also found errors in the lists of the «Muizz al Ansab». These include the erroneous genealogy of Arabshah, Abulkhair Khan, and their descendants, as well as errors in the genealogy of Dervish Khan.